Maintaining remission of ulcerative colitis with the probiotic Escherichia coli Nissle 1917 is as effective as with standard mesalazine. Issue 11 (11th October 2004) - Kruis, W; Frič, P; Pokrotnieks, J; Lukáš, M; Fixa, B; Kaščák, M; Kamm, M A; Weismueller, J; Beglinger, C; Stolte, M; Wolff, C; Schulze, J
Abstract : Background and aim: Evidence exists for the pathogenic role of the enteric flora in inflammatory bowel disease. Probiotics contain living microorganisms which exert health effects on the host. We compared the efficacy in maintaining remission of the probiotic preparation Escherichia coli Nissle 1917 and established therapy with mesalazine in patients with ulcerative colitis. Patients and methods: In total, 327 patients were recruited and assigned to a double blind, double dummy trial to receive either the probiotic drug 200 mg once daily (n = 162) or mesalazine 500 mg three times daily (n = 165). The study lasted for 12 months and patients were assessed by clinical and endoscopic activity indices (Rachmilewitz) as well as by histology. The primary aim of the study was to confirm equivalent efficacy of the two drugs in the prevention of relapses. Results: The per protocol analysis revealed relapses in 40/110 (36.4%) patients in the E coli Nissle 1917 group and 38/112 (33.9%) in the mesalazine group (significant equivalence p = 0.003). Subgroup analyses showed no differences between the treatment groups in terms of duration and localisation of disease or pretrial treatment. Safety profile and tolerability were very good for both groups and were not different. Conclusions: The probiotic drug E coli Nissle 1917 shows efficacy and safety in maintaining remission equivalent to the gold standard mesalazine in patients with ulcerative colitis. The effectiveness of probiotic treatment further underlines the pathogenetic significance of the enteric flora.